2024
DOI: 10.3390/su16051865
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Municipal Solid Waste Incineration Bottom Ash in Cement-Bound Mixtures

Szymon Węgliński,
Gabriel Martysz

Abstract: In order to protect the natural resources, it is beneficial for the environment when materials that are not valuable, such as waste or recycled materials, are used in engineering. This article presents laboratory studies on the use of mixtures of incineration bottom ash (IBA) from municipal waste incinerators with natural, fine grain and uniform aggregate in cement-bound layers. The mechanical and engineering properties of aggregates were studied, their usefulness was assessed and possible applications are ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that MSWI bottom ash can serve as a supplementary cementitious material in concrete and mortar mixes (Hossain et al [107]; Poon et al [108]). Furthermore, research has explored its effectiveness as a stabilizing agent for soft marine clay in road construction (Tam et al [109]). By incorporating MSWI bottom ash into construction practices, stakeholders can address waste management challenges while advancing sustainable construction objectives, thereby fostering a more circular and resilient built environment.…”
Section: • Sisal Fibersmentioning
confidence: 99%
“…Studies have shown that MSWI bottom ash can serve as a supplementary cementitious material in concrete and mortar mixes (Hossain et al [107]; Poon et al [108]). Furthermore, research has explored its effectiveness as a stabilizing agent for soft marine clay in road construction (Tam et al [109]). By incorporating MSWI bottom ash into construction practices, stakeholders can address waste management challenges while advancing sustainable construction objectives, thereby fostering a more circular and resilient built environment.…”
Section: • Sisal Fibersmentioning
confidence: 99%